Estudio de fortalezas y vulnerabilidades de los nuevos esquemas de autenticación en redes inalámbricas IEEE 802.11 - Mejia Fajardo, Marcela; Chaparro Vargas, Ramiro A. (Ingeniería, 2005)
The recent development of new confidentiality and data protection schemes in wireless local area networks (WLAN) IEEE 802.11 has encouraged outstanding improvements, including a new protocol hierarchy, in order to satisfy each one of the security services. This paper pretends to establish and analyze which are the strengths and weaknesses of the recent proposed model.